Pengaruh Organizational Citizenship Behaviours, Organizational Commitment Terhadap Job Performance Auditor - Rina Hartanti (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2021)
Abstract: Examining the Effect of Organizational Citizenship Behaviors and Organizational Commitments on Auditor’s Job Performance is the purpose of this study. The effect of each dimension of Organizational Citizenship Behaviors and Organizational Commitment on Auditor’s Job Performance was also tested in this study. Data was obtained by distributing 325 questionnaires to HRD Manager (Personnel Manager) at public accounting firms in DKI Jakarta to be forwarded to respondents, namely auditors and only 264 questionnaires were successfully filled out for analysis with Structural Equation Models (SEM). Research shows the results: (1). Auditor’s Organizational Commitment are proven to be positively and significantly influenced by Auditor’s Organizational Citizenship Behaviors (2). Organizational Commitment is proven to have a significant and positive effect on Job Performance. (3). Significantly and positively Organizational Citizenship Behaviors affect the Auditor's Job Performance. Auditors who have high Organizational Citizenship Behaviors ultimately provide maximum Job Performance at the public accounting firm where they work.